Open, High-Resolution EI+ Spectral Library of Anthropogenic Compounds - Price, Elliott J; Palát, Jirí; Coufaliková, Katerina; Kukučka, Petr; Codling, Garry; Vitale, Chiara Maria; Koudelka, Štěpán; Klánová, Jana (Frontiers in public health, 2021)
To address the lack of high-resolution electron ionisation mass spectral libraries (HR-[EI+]-MS) for environmental chemicals, a retention-indexed HR-[EI+]-MS library has been constructed following analysis of authentic compounds via GC-Orbitrap MS. The library is freely provided alongside a compound database of predicted physicochemical properties. Currently, the library contains over 350 compounds from 56 compound classes and includes a range of legacy and emerging contaminants. The RECETOX Exposome HR-[EI+]-MS library expands the number of freely available resources for use in full-scan chemical exposure studies and is available at: https://doi.org/10.5281/zenodo.4471217.
Keywords: expozom; electron ionization [EI+]; gas chromatography mass spectrometry; high-resolution; spectral library; Data Management; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; chemical exposure; Exposome; data management